2018
DOI: 10.1589/jpts.30.387
|View full text |Cite
|
Sign up to set email alerts
|

Limb-dominance and gender differences in the ground reaction force during single-leg lateral jump-landings

Abstract: [Purpose] The purpose of this study was to examine limb-dominance and gender differences in the magnitude of the ground reaction force during single-leg lateral jump-landings. We hypothesized that the peak ground reaction force would be larger in the non-dominant leg compared to that in the dominant leg and would be larger in females compared to that in men. [Subjects and Methods] Fifteen females and 15 males performed jump-landings sideways from a height of 20 cm, with a lateral distance of 60 cm. Vertical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 46 publications
(73 reference statements)
0
17
0
Order By: Relevance
“…It has already been reported that the landing ability of a single leg landing differs between dominant and non-dominant legs. 27 , 40 In this study, we only compared successful and unsuccessful trials, but stratified analysis based on dominance is necessary in the future. Finally, it has been reported that there are sex-related differences in vertical GRF maximum values during jump-landing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has already been reported that the landing ability of a single leg landing differs between dominant and non-dominant legs. 27 , 40 In this study, we only compared successful and unsuccessful trials, but stratified analysis based on dominance is necessary in the future. Finally, it has been reported that there are sex-related differences in vertical GRF maximum values during jump-landing.…”
Section: Discussionmentioning
confidence: 99%
“…The reliability of data collection using the following method has been reported in the past, and good reliability with ICC (1,1) between 0.73 and 0.74 have been confirmed. 26 , 27 …”
Section: Methodsmentioning
confidence: 99%
“…Oral questioning was used to confirm whether the knee that had undergone reconstruction was on the dominant side. The dominant limb was defined as the leg used to kick a ball to maximal distance [ 33 ]. The level of sports activity before injury was graded using the modified Tegner activity scale [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…Oral questioning was used to con rm whether the knee that had undergone reconstruction was on the dominant side. The dominant limb was de ned as the leg used to kick a ball to maximal distance 24 . The level of sports activity before injury was graded using the modi ed Tegner activity scale 25 .…”
Section: Measurementsmentioning
confidence: 99%